Pengukuran Kepuasan Pengguna Aplikasi Camscanner Menggunakan Metode End-User Computing Satisfaction (EUCS) - Siti Aminah; Joy Nashar Utamajaya (STMIK Budi Darma, 2023)
Communication technology plays an important role in our life. An example is the use of a communication technology called a smartphone. Smartphones can help people connect regardless of distance, space or time. Smartphones are crucial for students to support academic activities on campus. Often students get files in hardcopy form, so students will find it quite difficult to carry these files. With this problem students can take advantage of the CamScanner application on smartphones to scan all manual files into digital form without having to queue to the photocopying place. User satisfaction with system performance is a benchmark for implementing information technology. This study uses the End User Computing Satisfaction (EUCS) method to determine user satisfaction with the CamScanner application. To obtain data as research material, research questionnaires were distributed to employees by adopting the dimensions of the End User Computing Satisfaction method, namely the dimensions of Content, Accuracy, Format, Easy of Use and Timeliness. Data collection was carried out by distributing questionnaires to 72 Balikpapan students. It was found that the STMIK Borneo International Balikpapan students were very satisfied in using the CamScanner application. Based on the results of the tests that have been carried out, it shows that the percentage of all dimensions is above 80%, namely the Content dimension is 83.6%, the Accuracy dimension is 83.2%, the Format dimension is 83.3% , the Easy of Use dimension is 81.4% and the Timeliness dimension is 82.3% with dimensions that have a significant effect, namely the dimensions of Content, Accuracy and format